National accounts statistics of the Commonwealth of Dominica 1980-1993 (Central Statistical Office RoseauDM)
Provides estimates of gross domestic product in current and constant prices at factor cost; expenditure on GDP at current prices; gross national disposal income; and, appropriation and capital finance. Includes the balance of payments components from 1986 to 1993.
Located in the Statistics Section